2020
DOI: 10.7189/jogh.10.010402
|View full text |Cite
|
Sign up to set email alerts
|

Burden of influenza-associated respiratory and circulatory mortality in India, 2010-2013

Abstract: Burden of influenza-associated respiratory and circulatory mortality in India, 2010-2013 Background Influenza causes substantial morbidity and mortality worldwide, however, reliable burden estimates from developing countries are limited, including India. We aimed to quantify influenza-associated mortality for India utilizing 2010-2013 nationally representative data sources for influenza virus circulation and deaths. Methods Virological data were obtained from the influenza surveillance network of 10 laboratori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…They reported the median length of hospital stay of 3 d for IFB viral illness. An Indian study reported high influenza-associated mortality in children aged less than 5 years in addition to the elderly population[ 10 ]. Studies on the incidence, clinical burden, and economic impact of IFB helped to include an additional B strain in the vaccine against influenza.…”
Section: Epidemiology and Disease Burdenmentioning
confidence: 99%
“…They reported the median length of hospital stay of 3 d for IFB viral illness. An Indian study reported high influenza-associated mortality in children aged less than 5 years in addition to the elderly population[ 10 ]. Studies on the incidence, clinical burden, and economic impact of IFB helped to include an additional B strain in the vaccine against influenza.…”
Section: Epidemiology and Disease Burdenmentioning
confidence: 99%
“…Influenza causes significant pediatric mortality and morbidity globally, including in India [1][2][3]. Vaccines, including inactivated influenza vaccine (IIV) and live attenuated influenza vaccine (LAIV) formulations, are key to influenza prevention and control and have demonstrated moderate effectiveness when matched to circulating strains [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals and clinicians reported much more severe Influenza disease than they had seen previously and confirmed very high mortality rates [8]. Also, a study in 2013 reported that each year around 127,092 people die in India due to Influenza-associated respiratory and circulatory diseases [9]. WHO recommends the Influenza vaccine for high-risk groups such as pregnant women, children aged less than five years, the elderly, healthcare workers, and people who have chronic illnesses such as HIV/AIDS, asthma, diabetes, heart disease, or are immuno-compromised among others [10,11].…”
Section: Introductionmentioning
confidence: 73%